Implementasi MIT App Inventor untuk Aplikasi Translator Suara ke Teks di Platform Android - Gustiana Putri; Sularno (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2024)
MIT App Inventor, developed by the Massachusetts Institute of Technology (MIT), is an innovative platform for creating Android applications without requiring complex programming skills. The platform is popular for its user-friendly interface and the ability to quickly develop various mobile applications, such as a voice-to-text Translator. Utilizing voice recognition technology and Speech To Text (STT), MIT App Inventor enables users to convert speech into text and translate it into other languages. Beyond facilitating teaching and learning with its intuitive interface, the platform introduces basic programming concepts to students from diverse backgrounds, promoting digital inclusion and supporting innovation in mobile app development.